The instability of an export economy - Corea, Gamani 1925- (Colombo Marga Institute, 1975)
Study of the period 1930-1950.
Originally presented as the author's thesis, Oxford, 1952, with title: The economic structure of Ceylon in relation to fiscal policy.
Includes index.
Bibliography: p. [363]-368.
Keywords: Fiscal policy -- Sri Lanka; Sri Lanka -- Economic policy; Sri Lanka -- Economic conditions